2010
DOI: 10.17705/1jais.00243
|View full text |Cite
|
Sign up to set email alerts
|

Following the Sun: Temporal Dispersion and Performance in Open Source Software Project Teams

Abstract: Dispersion in working teams has been addressed by extant research mostly in terms of the physical distance that separates team members. Recently, the focus has shifted toward an examination of a newer construct-temporal dispersion (TD). The study of TD so far has been constrained mostly to conceptual work. This study furthers the understanding of TD through an empirical investigation of its relationship with open source software (OSS) team performance. In this paper, hypotheses are developed based on coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 100 publications
(116 reference statements)
0
37
0
Order By: Relevance
“…First we control for the project size. In line with Colazo and Fang [4] we expect that larger FLOSS projects can offer new developers much more possibilities to add or modify functionality than small projects can. Moreover, we control for FLOSS projects' age.…”
Section: Hypotheses Developmentmentioning
confidence: 53%
See 1 more Smart Citation
“…First we control for the project size. In line with Colazo and Fang [4] we expect that larger FLOSS projects can offer new developers much more possibilities to add or modify functionality than small projects can. Moreover, we control for FLOSS projects' age.…”
Section: Hypotheses Developmentmentioning
confidence: 53%
“…In line with previous evaluations by Colazo and Fang we quantify the project size (proj_size t ) by the amount of lines of code in t (LoC t ) [4]. For measuring project age (proj_age t ), we follow Singh et al and count the number of months between its inception and t (NoM t ) [24].…”
Section: Methodsmentioning
confidence: 99%
“…Geography barriers involve spatial, temporal, cultural, work and organizational dispersions (Smite et al, 2010). The spatial distance leads to a decrease in communication frequency (Colazo and Fang, 2010;Sosa et al, 2002) and technical team performance (Gopal et al, 2011), an increase in coordination problems (Lanubile et al, 2010;Nguyen-Duc et al, 2015) and a difficulty in communication and coordination related to culture and language difference between teams (Aubert et al, 2011;Gurung and Prater, 2006). Spatial distance is a nonlinear factor for communication in PD projects (Allen, 1997;Carmel and Abbott, 2007).…”
Section: Coordination and Communication In Gpd Projectsmentioning
confidence: 99%
“…Here, too, there have been conflicting findings about the effect of team dispersion on work quality. Although some studies suggested that dispersion has a negative effect on the quality of GDTs' work [Espinosa et al 2007a;Gopal et al 2011], others found that dispersion has no significant effect on work quality [Cataldo 2010] and may even lead to better work quality, as dispersion allows developers to take time to focus on the problems at hand [Colazo and Fang 2010]. Investigating 80 GDTs, Siebdrat et al [2009] concluded that the overall effect of dispersion is not necessarily detrimental but rather depends on the team's task-related process, including those that help coordinate 5:12 J. Sutanto et al Fig.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%